2019
DOI: 10.1007/s12253-019-00610-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Breast Cancer and Insulin Resistance on PD1 and TIM3 Expression in Peripheral Blood CD8 T Cells

Abstract: Epidemiological evidence points to a link between insulin resistance (IR) and breast cancer (BrCA). Insulin plays a role in CD8+ T cells (CD8T) differentiation and function and affects adipocytokines levels. CD8T activity in BrCA is associated with favorable outcome; while PD1 and TIM3 are markers of CD8T exhaustion and play critical roles in the negative regulation of T cell responses. Patients with (BrCA) have high expression levels of PD1 on circulating. Therefore, we hypothesized that BrCA and IR could aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…A recent study showed that TIM3 + CD8 + T cells may sustain the potential for IFN- γ production but lose cytotoxic activity in ovarian cancer [ 22 ]. Also, insulin resistance could induce the frequency of TIM3 expressing CD8 + T cells in breast cancer [ 23 ]. In our study, there was a significant increase in the TIM3 expression on CD8 + T cells in obese patients compared with HCs, and we found the positive correlation between TIM3 expression on CD8 + T cells and BMI, body fat percentage, and hip circumference.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that TIM3 + CD8 + T cells may sustain the potential for IFN- γ production but lose cytotoxic activity in ovarian cancer [ 22 ]. Also, insulin resistance could induce the frequency of TIM3 expressing CD8 + T cells in breast cancer [ 23 ]. In our study, there was a significant increase in the TIM3 expression on CD8 + T cells in obese patients compared with HCs, and we found the positive correlation between TIM3 expression on CD8 + T cells and BMI, body fat percentage, and hip circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Treg proportion in the DA lesions was significantly increased in all patients (p < 0.05) ( Figure 3A). Programmed cell death protein 1 (PD-1)-, T cell immunoglobulin domain and mucin domain-3 (TIM-3)or lymphocyte activation gene 3 (LAG-3)-positive T cells are recognized as exhausted subsets (27)(28)(29). Compared to those in PBMCs, the proportions of TIM-3+ CD4+ T cells (p < 0.05) and PD-1+ CD8+ T cells (p < 0.01) were remarkably higher in tumor sites ( Figure 3A).…”
Section: T Cells Are Exhausted and Tregs Are Increased In The Diffusmentioning
confidence: 99%
“…Besides HLA-G and ILT-2, additional IC molecules such as programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated protein (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), and CD95 are associated in tumor-driven immune escape mechanisms acting locally at the tumor site or systemically in the peripheral blood (24)(25)(26). The continuous upregulation and co-expression of multiple IC, being often observed in cancer and chronic infections, are indicative for an immunosuppressive/exhausted phenotype of T cells and are associated with loss of effector functions and immunosurveillance (27,28).…”
Section: Introductionmentioning
confidence: 99%